Pathological study of Pasteurella Multocida Recombinant Clone ABA392 - Mohammed Al Mohaini, Arshad Farid, Muhammad Muzammal, Arezoo Dadrasnia, Abdulkhaliq J. Alsalman, Maitham A. Al Hawaj, Yousef N. Alhashem, Salmah Ismail, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: In current study Molecular analysis of the recombinant clone ABA392 was carried out Methodology. In this study, detailed molecular analysis of the recombinant clone ABA392 were carried out by examining plasmid stability, plasmid profiling, determination of the plasmid molecular weight, and restriction endonuclease analysis. Results: From the experiments above, the plasmid size of ABA392 was estimated as 3.5 kb, while the size of the insert gene of ABA392 was estimated as 0.8 kb (double digested with PstI and SmaI restriction enzymes). A Pathogenicity study of recombinant clone ABA392 was carried out via a mouse virulence test and histopathological analysis, where it was found that mice, which were challenged with ABA392 and the parent strain of Pasteurella multocida serotype B strain PMB202, were lethal within 24 to 72 hours upon inoculation. Based on microscopic examination, the virulence effect was observed by marked haemorrhage in lung, liver, spleen, and kidney tissues. Conclusion: This study has also proven that the plasmid of recombinant clone ABA392 was stably maintained in the Escherichia coli JM101 host system as reported previously. A preliminary protein analysis via SDS-PAGE was performed and a distinct protein band was most likely to be detected, which was approximately 16kD. Nonetheless, further characterization of the recombinant clone ABA392 proteins needs to be done to determine the nature of these proteins, which are involved in the virulence mechanism of hemorrhagic septicemia.